2015
DOI: 10.5539/mas.v9n8p371
|View full text |Cite
|
Sign up to set email alerts
|

Vertical-Flow Constructed Wetlands in Cooperating with Oxidation Ponds for High Concentrated COD and BOD Pig-Slaughterhouse Wastewater Treatment System at Suphanburi-Provincial Municipality

Abstract: Oxidation Pond (OP) as engineering tool is generally used for treating the pig slaughterhouse wastewater which normally contains high concentration of COD and BOD in effluent. Unfortunately, it cannot reduce the organic substance (blood, hairs, grease, meats, solid dunks and some contaminants) from pig slaughtering areas under the 2-consecutive oxidation ponds by producing the minimum values of COD 151.92 mg/L, BOD 79.14 mg/L, coliform bacteria 2.6 x 10 -5 MPN/100mL, and fecal bacteria 1.5 x 10 -5 MPN/100mL bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…One study showed that SSFCW followed by anaerobic stabilization ponds system had significant removal of BOD, COD, and TSS; and it was more efficient in TSS and nutrient removal than classic systems (Gholizadeh et al, 2015). An oxidation pond-CW integrated system showed effective reduction of COD, BOD and bacteria from Pigslaughterhouse wastewater (Pitaktunsakul et al, 2015). A CW with an attached microbial growth Bio-hedge system enhanced the stability and performance in organic matter and nutrients removal with 33-67% lower HRT compared to conventional CW (Valipour et al, 2015).…”
Section: Zapatermentioning
confidence: 99%
“…One study showed that SSFCW followed by anaerobic stabilization ponds system had significant removal of BOD, COD, and TSS; and it was more efficient in TSS and nutrient removal than classic systems (Gholizadeh et al, 2015). An oxidation pond-CW integrated system showed effective reduction of COD, BOD and bacteria from Pigslaughterhouse wastewater (Pitaktunsakul et al, 2015). A CW with an attached microbial growth Bio-hedge system enhanced the stability and performance in organic matter and nutrients removal with 33-67% lower HRT compared to conventional CW (Valipour et al, 2015).…”
Section: Zapatermentioning
confidence: 99%